Diplomasi Ekonomi Indonesia Dalam Meningkatkan Hilirisasi Industri Nikel Pasca Larangan Ekspor Bijih Nikel (2020-2024) - Anindita, Tantri Maria; Simanjuntak, Triesanto Romulo; Seba, Roberto Octavianus Cornelis (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2025)
This study describes Indonesia's economic diplomacy strategy for promoting the nickel industry downstream following the implementation of the nickel ore export ban policy in 2020. The author will review Indonesia's economic diplomacy efforts or strategies in promoting the nickel industry downstream following the 2020 nickel ore export ban using the concepts of economic diplomacy and dependency theory. The author employs a qualitative approach through a literature review. This study found that Indonesia's economic diplomacy employs a combination of bilateral and multilateral approaches, including establishing cooperation with key partners such as China and South Korea. This diplomacy is carried out to maintain the downstream policy and attract foreign investment to develop the nickel processing sector. Despite facing challenges from the European Union through the WTO, Indonesia remains determined to maintain this policy aiming to create domestic added value and reducing dependence on raw material exports. These findings demonstrate how economic diplomacy serves as an effective instrument in achieving Indonesia's national interests.